Suppose 5*a + 2*n + 3 = 0, 4*a - 2*a + 4*n - 2 = 0. Let r(s) = -4*s + 1. Let f be r(a). Let j = 9 - 6. Solve 10 = -f*h + j*h for h.

-5

Let y be (0 + -1)/((-3)/6). Solve 13 = y*o + 5 for o.

4

Let x(i) = i**2 - 2*i - 2. Let b be x(-2). Solve -q - q = b for q.

-3

Let u(p) = -p3 - 3*p2 - p + 1. Let a be u(-3). Suppose b = 5*b - a. Solve 0 = -q - b - 2 for q.

-3

Let k = -4 + 8. Let v(t) = -t3 + 2*t2 - 2*t + 1. Suppose -z - 3*p + 9 = 2, -z + 3 = p. Let f be v(z). Solve -x - k + f = 0 for x.

-4

Let m = -4 + 33. Suppose 0 = 3*z - m - 16. Solve -l = 4*l + z for l.

-3

Let n = 41 + -11. Solve -5*g - 10 = -n for g.

4

Let x be ((-52)/8 - -3)*-2. Suppose 2 + x = 3*v. Solve v*z + 3 + 6 = 0 for z.

-3

Suppose 28 - 7 = 3*s. Solve -6*k - 1 = -s*k for k.

1

Let z(o) = 2*o3 + o2 + 2o + 1. Let r be z(-2). Let n be 10/r(-21)/2. Solve -3 = -4*u - n for u.

-1